Laser land leveling for enhancing water productivity at field level - Rajput, T B S; Patel, Neelam (Indian Farming, 2020)
Efficient water utilization is the need of the time in India in view of the limited water resources and increasing water demand from agriculture as well as from other sectors. Enhancement of agricultural water productivity is essential as agriculture consumes a lion’s share of freshwater resources. Precise land leveling is a prerequisite for enhancing agricultural water productivity as it minimizes percolation and surface runoff losses. Use of proper stream size also helps in achieving high water distribution uniformity. Land leveling is essential for scientific water management not only in water scarce areas but also in canal command areas. The investigations on impact of laser land leveling on water productivity and wheat yields were conducted in selected villages in Uttar Pradesh and are presented in the article.